The Influence Of A Socio-Emotional Approach In The Learning Process Of Student Affairs - Yusuf, Yusuf; Hakim, Lukman; Khumayah, Khumayah (JPT : Jurnal Pendidikan Tematik, 2020)
The research location at MI NU Manafiul Ulum I using a questionnaire method and supported by the results of documentation to students as many as 30 people and data analysis techniques using a simple regression test formula. The results of this study are: (1) The socio-emotional approach technique in the Akidah Akhlak Subject at MI NU Manafiul Ulum I is in the good category, it can be seen from the analysis that shows an average value (mean) of 85.3 which is included in the interval 75-86, meaning that the socio-emotional approach to the Akidah Akhlak Subject is carried out effectively. (2) Students 'moral abilities in the Akidah Akhlak Subject at MI NU Manafiul Ulum I are in the good category, it can be seen from the analysis that the mean value of students' Morals is 86.33 which is included in the 84- 95. So, the better the Students' Morals in the Akidah Akhlak Subject, the easier it is for the teacher to deliver the learning material being taught. (3) There is a positive and significant relationship between the Relationship between the Socioemotional Approach and the Students' Morals in the kidah Akhlak Subject. This is evident from the results of the regression analysis which shows that at the 5% significant level there is r table = 0.361 while ro = 0.721 which means that ro is greater than rt (ro> rt) so Ho is rejected and Ha is accepted.